181 Perioperative Morbidity of Feminizing Gender Affirmation Surgery: Analysis of the National Surgical Quality Improvement Program (NSQIP) Database. Issue 1 (1st April 2022) - Walton, A.; Pandit, A.; Payakachat, N.; Mundinger, G.; Raheem, O.; Benson, C.
ABSTRACT: Introduction: Genital Gender Affirmation Surgery (gGAS) has become increasingly prevalent as a result of increasing insurance coverage and surgeon availability throughout the US. Objective: To characterize the demographics, trends, and perioperative morbidity of feminizing gGAS among transgender patients in the US using a population data. Methods: The National Surgical Quality Improvement Program (NSQIP) database was queried to perform retrospective analysis of feminizing gGAS between 2006-2019. Due to a lack of standardized CPT codes for feminizing gGAS, we identified our initial cohort using individual common CPT codes for gGAS, associated with ICD Codes for gender dysphoria. We further differentiated primary gGAS from revision cases by requiring penectomy (CPT 54120/54125) and one vaginoplasty code (CPT 57291, 57291, 57335, 55970) to be included. We characterized baseline demographics, perioperative characteristics, and 30-day complications. Results: 141 transgender patients underwent feminizing gGAS from 2016-2019, after excluding 285 patients, as none were documented before 2016. The majority of cases were in 2018 (n=57, 40.4%) and 2019 (n=41, 29.1%). Most patients were operated on by plastic surgery (85%), compared to urology (15%). Mean age was 39.6 years (SD=13.8), and mean BMI was 26.3 (SD=5.5). Gender was classified as female (77.3%), male (22.7%) and non-binary (0.7%). 78% were white, 7.8% African American, 7.1% Asian, and 7.1% other. The most common co-morbidities were hypertension (7.8%), diabetes (6.4%), and smoking (5%). The mean operative time was 339 min (SD=85.7min) and mean hospitalization was 6.1 days (range 3-24 days). There were 14.6% with ³1 complication (14.6%). Wound disruption occurred in 12 patients (8.5%), 4 (2.8%) UTIs, 3 (2.1%) superficial wound infections and 1 (0.7%) deep wound infections, and 3 (2.1%) required blood transfusion. Among 12 patients (8.5%) that returned to OR (average of 12.6 days), 50% for wound disruption and 6 patients were readmitted at mean 19.4 days from surgery. Conclusions: This is the first characterization of patients undergoing femininizing gGAS utilizing the NSQIP database. There continues to be increasing volume of patients undergoing primary gGAS, which appears to be safe with acceptable rates of complications and reoperations. Further study utilizing claims-based population databases may provide a better understanding of the scope of feminizing gGAS. Disclosure: No